Evaluating The Amount of "Hash Tag", "Like", "Comments", And "Followers", on Daily Food Blogger Posting on the Occurrence of "Repeated Orders", From Client on Promotion Media Instagram - Christiantie Mandasari, Monica; Permadi Iskandar, Budi (The Indonesian Journal of Business Administration, 2016)
Abstract. Social media also now become the means or the digital activities of marketing, Digital marketing is a form of business to promote and market a product with the use of digital media, such as the Internet. Digital marketing will generate interaction between producers, market intermediaries, and consumers. Food bloggers using digital marketing in promoting and marketing a product. Food bloggers not only use blogs to promote and market a product but also a social media using Instagram. Through this medium of social interaction between producers, market intermediaries, and consumers can be more active because instagram app can be installed exclusively on a personal mobile phone that can be taken anywhere. Food bloggers use some strategies in promoting and marketing culinary products on social media instagram. Repeated orders from people who want their products marketed by food bloggers can occur through such interactions.Â Keywords:Â  Culinary, Digital Marketing, Food Blogger, Instagram, Online Marketing